2021
DOI: 10.1111/bph.15486
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural and pharmacological effects of cannabidiol (CBD) and the cannabidiol analogue KLS‐13019 in mouse models of pain and reinforcement

Abstract: Background and Purpose: Cannabidiol (CBD) is a non-euphorigenic component of Cannabis sativa that prevents the development of paclitaxel-induced mechanical sensitivity in a mouse model of chemotherapy-induced peripheral neuropathy (CIPN).We recently reported that the CBD structural analogue KLS-13019 shows efficacy in an in vitro model of CIPN. The present study was to characterize the behavioural effects of KLS-13019 compared to CBD and morphine in mouse models of CIPN, nociceptive pain and reinforcement.Expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 35 publications
1
15
1
Order By: Relevance
“…Here, we found that pure CBD alone had little impact on acute pain associated with CIPN. This is in contrast to several other studies that have found that CBD can reduce neuropathic pain in animal models [ 10 , 12 , 19 ]. An important difference between our study and the previous work is that we are looking at the acute effects of CBD administration as compared to those studies that looked at more prolonged effects of CBD treatment.…”
Section: Discussioncontrasting
confidence: 95%
“…Here, we found that pure CBD alone had little impact on acute pain associated with CIPN. This is in contrast to several other studies that have found that CBD can reduce neuropathic pain in animal models [ 10 , 12 , 19 ]. An important difference between our study and the previous work is that we are looking at the acute effects of CBD administration as compared to those studies that looked at more prolonged effects of CBD treatment.…”
Section: Discussioncontrasting
confidence: 95%
“…A second major goal of these studies was to test if changes in GPR55 IR area were reversible after treatment with KLS-13019, a novel compound that has been shown to reverse mechanical allodynia in paclitaxel-treated mice (Foss et al 2021). To test for reversibility of paclitaxel-induced increases in cell body GPR55 IR area, DRG cultures were pre-treated for 8 hours with 3 mM paclitaxel and then the cultures were co-treated for an additional 16 hours with various concentration of KLS-13019 in the continuing presence of paclitaxel.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, we and others have demonstrated that CBD and other non-psychoactive cannabinoids are effective in animal models of spinal cord injury-associated neuropathic pain (Li et al 2018). However, CBD has limitations in terms of potency, e cacy, safety, and oral bioavailability (Brenneman et al 2018;Foss et al 2021). With the recognition that optimization of CBD was warranted, the development of analogues of CBD was undertaken with the eventual emergence of KLS-13019 (Kinney et al 2016), a novel compound that has been shown to be effective in both the prevention and reversal of allodynia in a mouse model of CIPN (Foss et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Administration of cannabidiol or its analogue (KLS‐13019) prior to administration of paclitaxel reduced mechanical allodynia on the 14th day. Furthermore, treatment with the analogue (20 mg/kg, i.p), but not with cannabidiol (20 mg/kg, i.p) administered on the 12th, 13th, and 14th day in animals sensitized with paclitaxel, showed antinociceptive activity [30] . Our results reinforce the antiallodynic activity of CBD analogue and cannabidiol in the prevention of paclitaxel‐induced neuropathy and could serve as a basis for the development of new substances with better analgesic efficacy in models of chronic pain.…”
Section: Resultsmentioning
confidence: 94%